Template-stripped, ultraflat gold surfaces with coplanar, embedded titanium micropatterns - Venkataraman, Nagaiyanallur V (Langmuir : the ACS journal of surfaces and colloids, 2013)
Ultraflat gold surfaces with coplanar, embedded titanium micropatterns, exhibiting extremely low roughness over the entire surface, have been obtained by a modified template-stripping procedure. Titanium is deposited onto photolithographically predefined regions of a silicon template. Following photoresist lift-off, the entire surface is backfilled with gold, template stripping is conducted, and an ultraflat micropatterned surface is revealed. Atomic force microscopy confirms a roughness of <0.5 nm RMS on both Ti and Au regions, with a topographically indistinguishable gold-titanium interface. Detailed surface-chemical maps of the patterned surfaces have been obtained by means of imaging X-ray photoelectron spectroscopy (i-XPS) as well as time-of-flight secondary-ion mass spectrometry (ToF-SIMS). They confirm the presence of well-separated Ti and Au regions, with a chemical contrast that is sharp (as determined by ToF-SIMS) and complete (as determined by i-XPS) across the Ti-Au interface. Thus, a surface has been fabricated that is physically homogeneous down to the nanoscale incorporating chemically distinct micropatterns consisting of two different metals, with totally contrasting surface chemistries